Development of Ecotourism Packages in Karang Sidemen Tourism Village, Central Lombok - Hastuti, Widya; Rumba; Supardi (Journal of Mandalika Review, 2024)
Abstract Introduction: The Karang Sidemen tourist village has an ecotourism package called Begerusuk Adventure, but in this tour package there are still not enough ecotourism activities on offer, therefore, an ecotourism package is being developed that will later add ecotourism activities. This research aims to find out the actual conditions of the Karang Sidemen tourist village, which is devoted to aspect 5A (Accessibility, Accommodation, Amenities, Attraction, and Activity), to find out the actual conditions of ecotourism packages, and to find out recommendations for ecotourism packages in the Karang Sidemen Tourism Village. Methodology: The research method used in this study is qualitative. This research covers attractions, accessibility, accommodation, amenities, activities, and conditions of ecotourism packages by involving 5 informants, namely, the Deputy Chair of the Karang Sidemen Tourism Village Pokdarwis, the owner of Datu Craft MSMEs, the owner of Andewi Homestay, and tourists. Findings: There is already a previous tour package, namely the Begerusuk Adventure package, which still lacks ecotourism activities on offer, therefore there is a recommendation for an ecotourism package that will later add ecotourism activities such as making eco prints, visiting MSMEs, and planting tree seedlings. Conclusion: Based on the identification of ecotourism potential and the actual condition of the existing ecotourism packages in Karang Sidemen Tourism Village, it is concluded that they are good but need further development. The development proposed by the researcher includes adding activities such as creating eco prints, visiting local MSMEs, and planting tree seedlings. Keywords: Development, Ecotourism, Tourism Packages, Tourism Village